Analysis on the Effect of Metformin Hydrochloride Combined with Insulin Pump for Gestational Diabetes Mellitus - Xinghua Li; Guilian Li; Yan Liu; Fanchun Meng; Lihong Han; Yuanyuan Shao (Tehran University of Medical Sciences, 2022)
Background: U To analyze the effect of metformin hydrochloride combined with insulin pump for gestational diabetes mellitus (GDM). Methods: Overall, 216 patients with GDM in Zhangqiu Maternity and Child Care Hospital, Jinan, China from Aug 2018 to Dec 2020 were enrolled and randomized into research and control groups. Patients in the control group were treated with insulin pump, while those in the research group were treated with metformin hydrochloride combined with insulin pump. The clinical efficacy, blood glucose levels, serum Betatrophin, C reactive protein (CRP), Cystatin C (Cys-C), homocysteine (Hcy), adiponectin, tumor necrosis factor (TNF-α), interleukin-6 (IL-6) content, incidence of adverse pregnancy outcomes and incidence of adverse newborns of patients in the two groups were compared. Results: After treatment, the total clinical efficiency of the research group was 84.26%, significantly higher than that of the control group (68.52%). The levels of FPG, 2hPG, HbAlc, serum Betatrophin, CRP, CysC, Hcy, adiponectin factors, TNF-α, and IL-6 in the research group were lower than those in the control group, with statistically significant differences (P<0.05). The overall incidence of adverse pregnancy outcomes was 10.19% in the research group, and 25.93% in the control group. The comparative differences between the two groups were statistically significant (P<0.05). The overall incidence of adverse newborns was 9.26% in the research group, and 21.30% in the control group. The comparative differences between the two groups were statistically significant as well (P<0.05). Conclusion: Metformin hydrochloride combined with insulin pump for GDM can significantly reduce blood glucose level, regulate serum protein factor levels, and improve adverse outcomes for mother and child, which deserves clinical promotion.